Fanconi Bickel Syndrome: Novel Mutations in GLUT 2 Gene Causing a Distinguished Form of Renal Tubular Acidosis in Two Unrelated Egyptian Families - Mohammad Al-Haggar; Osamu Sakamoto; Ali Shaltout; Amany El-Hawary; Yahya Wahba; Dina Abdel-Hadi (Case Reports in Nephrology, 2011)
Background. Fanconi-Bickel syndrome (FBS) is an autosomal recessive disorder caused by defects in facilitative glucose transporter 2 (GLUT2 or SLC2A2) gene mapped on chromosome 3q26.1-26.3, that codes for the glucose transporter protein 2. Methods. Two unrelated Egyptian families having suspected cases of FBS were enrolled after taking a written informed consent; both had positive consanguinity, and index cases had evidences of proximal renal tubular defects with hepatomegaly; they were subjected to history taking, signs of rickets as well as anthropometric measurements. Laboratory workup included urinalysis, renal and liver function tests including fasting and postprandial blood sugar; serum calcium, phosphorus, alkaline phosphatase, sodium and potassium, lipid profile, and detailed blood gas. Imaging including bone survey and abdominal ultrasound, and liver biopsy were done to confirm diagnosis. Molecular analysis of the GLUT2 gene was done for DNA samples extracted from peripheral blood leukocyte. All coding sequences, including flanking introns in GLUT2 gene, were amplified using PCR followed by direct sequencing. Results. Two new mutations had been detected, one in each family, in exon 3 two bases (GA) were deleted (c.253 254delGA) and in exon 6 in the second family, G-to-C substitution at position-1 of the splicing acceptor site (c.776-1G>C or IVS5-1G>A). Conclusion. FBS is a rare disease due to mutation in GLUT2 gene; many mutations were reported, about half were novel mutations; yet none of these mutations is more frequent. A more extensive survey for the most frequent mutations among FBS has to be contemplated to allow for use of molecular screening tests like ARMS.